2014
DOI: 10.1016/j.cellsig.2014.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Redox control of p53 in the transcriptional regulation of TGF-β1 target genes through SMAD cooperativity

Abstract: Transforming growth factor-β1 (TGF-β1) regulates the tissue response to injury and is the principal driver of excessive scarring leading to fibrosis and eventual organ failure. The TGF-β1 effectors SMAD3 and p53 are major contributors to disease progression. While SMAD3 is an established pro-fibrotic factor, the role of p53 in the TGF-β1-induced fibrotic program is not clear. p53 gene silencing, genetic ablation/subsequent rescue, and pharmacological inhibition confirmed that p53 was required for expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
123
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 90 publications
(133 citation statements)
references
References 32 publications
10
123
0
Order By: Relevance
“…More recent studies have further verified the role of p53 in AKI by testing renal tubule-specific p53 ablation mouse models 51, 52 . Interestingly, CKD may also be associated with the increase or activation of p53 as a consequence of TGF-β up-regulation or PTEN down-regulation 53, 54 . Such “pre-activation” of p53, though at low to moderate levels, may greatly enhance tubular damage upon AKI.…”
Section: Potential Mechanisms Underlying the Susceptibility Andmentioning
confidence: 99%
“…More recent studies have further verified the role of p53 in AKI by testing renal tubule-specific p53 ablation mouse models 51, 52 . Interestingly, CKD may also be associated with the increase or activation of p53 as a consequence of TGF-β up-regulation or PTEN down-regulation 53, 54 . Such “pre-activation” of p53, though at low to moderate levels, may greatly enhance tubular damage upon AKI.…”
Section: Potential Mechanisms Underlying the Susceptibility Andmentioning
confidence: 99%
“…Lots of evidences have shown that activation of TGF-β signaling (especially TGF-β1 signaling) plays a central role in the pathogenesis of renal fibrosis222232425. TGF-β1 promotes ECM production by activating type I and type II serine/threonine kinase receptors26.…”
Section: Discussionmentioning
confidence: 99%
“…Increased PAI-1 expression, due to increased TGF-β1 in the injured tissue, initiates and perpetuates the fibrotic cycle. The need for novel targeted approaches for the treatment of fibrosis highlights the clinical potential in the current probe of molecular mechanisms underlying TGF-β1-regulated PAI-1 gene control [13]. …”
Section: Interstitial Fibrosismentioning
confidence: 99%
“…The collective research efforts in the CCBCR resulted in the identification of a novel pathway of TGF-β1-initiated fibrotic gene expression in an in vivo model of renal injury that mimics obstructive uropathy in humans [summarized in 14]. While TGF-β1-induced SMAD2/3 signaling is a critical event in the progression of chronic kidney disease, the role of non-SMAD mechanisms in the orchestration of fibrotic gene changes remain largely unexplored yet constitute likely targets that could be exploited for clinical gain.…”
Section: Interstitial Fibrosismentioning
confidence: 99%